Evaluation of the anticoagulant effect of rivaroxaban and its influence on coagulation tests in patients treated for venous thromboembolism - Góralczyk, Tadeusz (2017)
Rivaroxaban is a direct oral anticoagulant (DOAC), activated factor X (FXa) inhibitor. The aim of this dissertation was to assess the variability of rivaroxaban-induced anticoagulant effect over time as well as the identification of demographic and clinical factors influencing rivaroxaban levels in patients with venous thromboembolism (VTE). The impact of rivaroxaban on routine coagulation tests and assays used for the diagnostics of thrombophilia was also evaluated.Concentrations of rivaroxaban were determined by a chromogenic assay based on FXa inhibition. Routine coagulation tests and tests for the diagnostics of thrombophilia were performed using standard methods as recommended by the manufacturers.Blood collection at least 24 hours since the last dose of rivaroxaban has been shown to prevent from the false-positive results for lupus anticoagulant. Rivaroxaban up to 300 ng/ml had no influence on activated protein C resistance assay based on diluted Russell's viper venom time. It has been found that the DOACs, especially rivaroxaban (at the dose of 20 mg once daily) can be safely used in patients with VTE and antiphospholipid syndrome. Under routine conditions, prothrombin time and activated partial thromboplastin time are not useful for detecting the presence of rivaroxaban in a sample.
Keywords: coagulation tests; Rivaroxaban; anti-coagulation